Synthesis and Characterization of Hydroxyapatite/Alginate Composites: Study of pH and Sintering Influenced on the Structural, Morphological, and Clindamycin Release Behavior - Wulandari, Wulandari; Islami, Dini Muthi'ah; Jamarun, Novesar; Wellia, Diana Vanda; Emriadi, Emriadi (Universitas Gadjah Mada, 2024)
The hydroxyapatite/alginate (HAp/Alg) composite was synthesized using an in-situ precipitation route. The effect of pH (8, 9, 10, and 11) and calcination temperature (300, 500, 700, and 900 °C) were studied by characterization techniques such as X-ray diffraction (XRD), Fourier-transform infrared (FTIR), and scanning electron microscopy with energy-dispersive X-ray (SEM with EDAX). XRD results show the hexagonal crystal system of HAp for each pH value and the biphase (HAp and whitelockite) for the sintering temperature at 700 and 900 °C. The FTIR spectra show no impurity peaks. SEM images revealed spherical-like (HAp/Alg-11) and flake-like (HAp/Alg-900) particles with good homogeneity, size, and shape that could be notable for biomedical utilization, such as drug delivery material. Drug loading and release ability of pure HAp, HAp/Alg-11, and HAp/Alg-900 composites have been investigated with clindamycin hydrochloride as the drug model. The maximum clindamycin HCl release from HAp, HAP/Alg-11, and HAp/Alg-900 reached 74.48, 92.75, and 69.65% in the 8th hour. HAp/Alg-11 has the highest release because it has the largest surface area of 162.584 m2/g. Antibacterial test results showed HAp/Alg-11 has antibacterial activity against Staphylococcus aureus and Escherichia coli, confirming that HAp/Alg-11 composite has the potential to be applied as drug delivery.